Detection of Lactobacillus and Gardnerella species in vaginal samples by PNA-FISH - Machado, António (2012)
Bacterial vaginosis (BV) is a common vaginal infection of women in reproductive age. This infection is initially asymptomatic and late diagnosis can increase the health costs and hamper treatment. Therefore, an easy and quick method to accurately detect the transition between normal microflora to the predecessors of infection is of upmost importance. Despite the fact that BV etiology remains unknown, it is commonly accepted that the microbial switch from normal to BV state is characterized by a decrease in vaginal colonization by Lactobacillus species together with an increase in the number of Gardnerella vaginalis and others anaerobes. G. vaginalis is found in normal vaginal epithelium but recent findings suggested that G. vaginalis biofilm can be responsible for the establishment of BV, allowing other anaerobes to grow. In this work, our goal was to develop two novel Peptid Nucleic Acid (PNA) probes for Fluorescence in situ Hybridization (FISH) multiplex analysis, aimed to detect Lactobacillus spp. and G. vaginalis in vaginal samples. We designed, evaluated and validated both probes by using 36 representative Lactobacillus strains, 22 representative Gardnerella vaginalis strains and 27 others taxonomically related or pathogenic bacteria strains usually found in vaginal samples. The probes were also tested in 17 vaginal samples, collected from women with normal vaginal microflora or women with BV. These probes proved to be a powerful tool for the simultaneous detection and visualization of Lactobacillus spp. and G. vaginalis in bacterial strain collections and vaginal samples, with higher specificity and sensitivity than similar reported probes . More precisely, theoretical specificity and sensitivity from PNA probes were 99.65% and 91.50%, respectively, for Lactobacillus spp. and 99.9999% and 95.00%, respectively, for G. vaginalis.